ANALISIS PERTUMBUHAN ARUS PETIKEMAS DI TERMINAL PETIKEMAS SEMARANG - Arif, An Zaenal; Suwandi, Putri Anggi Permata; Kristiawan, Agung (Universitas PGRI Semarang, 2023)
Terminal Petikemas Semarang is one of the Terminals under the management of Subholding PT. Pelindo Terminal Petikemas which has a special pier or terminal for container ship activities, where the Terminal Petikemas Semarang area is in the Pelabuhan Tanjung Emas area, Semarang. The purpose of this study is to determine the growth of container flows at the Terminal Petikemas Semarang for the next 10 years, namely the period from 2023 to 2032 based on projections carried out using the regression method by correlating container flows and the Gross Regional Domestic Product (GRDP) index of Java Province Middle in the period 2013 to 2032.